Revisiting excess commuting and self-employment: The case of Latin America - José Ignacio Giménez-Nadal; Jorge Velilla; Raquel Ortega (Global Labor Organization (GLO), 2022)
This paper analyzes the commuting behavior of employee and self-employed workers in urban areas of eleven Latin American countries, within a theoretical framework that identifies employees' excess commuting as different from self-employed workers' commuting. Using data from the ECAF data, results show that employees spend about 8.2 more minutes commuting to work than their self-employed counterparts, net of observable characteristics, a difference of around 18.5% of the employees' commuting time. This difference is qualitatively robust across the eleven countries and is concentrated in commutes by public transit, but it is not explained by differences in access to public transit services between the two groups. This analysis is a first exploration of self-employed and employee workers' commuting time in Latin American countries. By analyzing differences in commuting time between these two groups of Latin American workers, our analysis may serve to guide future planning programs.
Keywords: R40; O57; 330; commuting time; self-employment; Latin America; ECAF data